Uji Fungsional Metode Ohmic Heating Terhadap Perubahan Mutu Madu Karet Pada Proses Pasteurisasi - Anang Lastriyanto; Sasongko Aji Wibowo; Khoiril Anam; Muhammad Amin Muzaki; Vincentia Veni Vera; Istifar Yogi Prayogi (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Honey is produced by bees in the form of a thick liquid and has a sweet taste derived from flower nectar. Heating honey aims to prevent the cooling process by reducing the water content in honey. Heating using an ohmic heater is carried out by passing an alternating current (AC) to the food which is a conductive material. The purpose of this study was to determine the level of heating, energy efficiency used, and changes in the quality of the honey content using several ohmic heating methods. The methodology used is the heating process is carried out until the honey temperature reaches 63°C, using 3 frequency variations, namely 250 Hz, 150 Hz, and 50 Hz. The results showed that testing using rubber honey using 3 frequency variations of the fastest temperature penetration rate was in the heating process using a frequency of 50 Hz which took 6 minutes with a penetration rate value of 10.5ºC/Minute. The smallest electric power and electric current using a frequency of 150 Hz. Heating honey using an ohmic heater using 3 frequency variations found that, does not affect the moisture content and the degree of brix value in honey.